(3cja JMVQ GdQSGdI GdLGeYjI (B:s (3GdebGdI(B-(3GdhQbI GdaUdjI(B-(3GdeTQhY(B-(3GdCWQhMI(B-(3GdJbOje hGdGdbGA(B-(3GdJbQjQ (B/s - (3GdOLGfj, YOfGf jhSas ((3YeGf(B: s (3OGQ hGFd ddfTQ(B, s, 2000)
(3GdhQbI GdaUdjI hGdebGdI(B- (3GdQSGdI hGdCWQhMI heTQhY GdJNQL(B- (3GdMdbGJ GdOQGSjI hCSGdjH GdGdbGA(B- (3GdJbQjQs
Keywords: (3GdHMhKs; (3GdJbGQjQ GdYdejIs; (3GdQSGFd GdLGeYjIs